RE-EXAMINATION OF BASES AND OPPORTUNITIES FOR APPLYING ACCOUNTING JUDGMENT. - Campfield, William L. (The Accounting Review, 1959)
Abstract The article highlights of the judgment forming process, some of the major non-accounting areas in which accountants have unparalleled opportunity for exercising broader and managerially useful judgments, and the outline of areas for increased emphasis by the accounting profession in training accountants for an enlarged judgmental role. Professional accountants have for many years furnished services to management with respect to opinions and advice on the reliability and fairness of historical financial data. Useful as this traditional service may be, it has less value to management as a planning and control device than many other mechanisms or techniques employed by business enterprise. The day is rapidly approaching when professional accountants can no longer afford the luxury of merely uncovering static facts and reporting them to management. The evolving nature of business enterprise over the past half century has been such that accountants who expect to occupy positions in or with respect to individual business enterprises must be prepared to exercise sound judgment in a variety of new, novel, and often perplexing situations confronting these enterprises.